Predictors of High Program Exposure Among Adolescents Participating in a Smoking Prevention Intervention in Romania. (April 2019) - Nădăşan, Valentin; Ferencz, Loránd; Ábrám, Zoltán; Foley, Kristie
Introduction: Web-based smoking prevention programs can be delivered to large groups of adolescents under relatively private conditions at a convenient cost, but their effectiveness is highly dependent on the level of exposure to the educational content. The objective of the study was to identify the predictors of high program exposure among a group of adolescents participating in a web-based smoking prevention cluster randomized trial in Romania. Methods: The study sample included 675 adolescents from Târgu Mureş, Romania. The level of exposure to the ASPIRE web-based smoking prevention program was monitored using data automatically saved on the system server. High program exposure was defined as watching 75% to 100% of the educational content. Associations between adolescents' sociodemographic, psychological, and behavioral variables collected online at the beginning of the intervention and high program exposure were tested using chi-square test and logistic regression. Results: In all, 68.3% of students were highly exposed to the program. There were 4 significant predictors of high program exposure in the multivariable logistic regression model: participant's father's lower level of education (odds ratio [OR]: 1.75; 95% confidence interval [CI]: 1.19-2.44), participant's brother's nonsmoking status (OR: 1.76; 95% CI: 1.13-2.72), never trying e-cigarettes (OR: 1.73; 95% CI: 1.22-2.45), and considering the health of others an important reason not to smoke (OR: 2.46; 95% CI: 1.54-3.93). Conclusions: The analysis identified sociodemographic, psychological, and behavioral factors that may be useful in project management of such intervention to improve program effectiveness.